2017
DOI: 10.3390/ijerph14101222
|View full text |Cite
|
Sign up to set email alerts
|

To Facilitate or Curb? The Role of Financial Development in China’s Carbon Emissions Reduction Process: A Novel Approach

Abstract: With the Paris Agreement coming into effect, China, as the largest CO2 emitter in the world, will be facing greater pressure to reduce its carbon emissions. This paper discusses how to solve this issue from the perspective of financial development in China. Although many studies have analyzed its impact on carbon emissions, the conclusions are contradictory. A major criticism of the existing studies is the reasonability of the selection of appropriate indicators and panel estimation techniques. Almost all stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 98 publications
3
44
0
Order By: Relevance
“…Various indexes have been adopted by scholars based on their research objectives and data availability. Earlier studies mostly used a single proxy variable; scholars now generally adopt a series of indictors or construct a comprehensive indicator based on several existing indexes and relevant statistical techniques to measure financial development [33][34][35], as the empirical results may depend on how financial development is measured [23,33].…”
Section: Data Selectionmentioning
confidence: 99%
“…Various indexes have been adopted by scholars based on their research objectives and data availability. Earlier studies mostly used a single proxy variable; scholars now generally adopt a series of indictors or construct a comprehensive indicator based on several existing indexes and relevant statistical techniques to measure financial development [33][34][35], as the empirical results may depend on how financial development is measured [23,33].…”
Section: Data Selectionmentioning
confidence: 99%
“…These studies include (Boutabba, 2014;Jamel & Maktouf, 2017;Li, Zhang, & Ma, 2015;Ozturk & Acaravci, 2013;Saboori, Sulaiman, & Mohd, 2012;Zhang, 2011), while some studies found a negative relationship between financial development and CO2 emissions. These studies include (Mulali, Tang, & Oztur, 2015;Saidi & Mbarek, 2017;Xing, Jiang, & Ma, 2017). In the fourth stage, financial development and industrial production positively contribute to economic growth (Ang, 2008;Kedourie, 2013;Lakhera, 2016;Malinvaud, 1979;Sent a, 1966;Shucheng, 2017;Swanson & Lin, 2009) .…”
Section: B the Relationship Between Remittances And Co2 Emissionsmentioning
confidence: 99%
“…Moreover, other works [38,39] admit that financial development improved the level of pollution. Park et al [40] also concur with the variation of the EKC after analyzing the effect of economic growth in association with toxic emissions.…”
Section: Literature Reviewmentioning
confidence: 99%